The screenwriter's bible : a complete guide to writing, formatting, and selling your script - Trottier, David (Los Angeles: Silman-James press, 2019)
"The Screenwriter's Bible's is one of the most popular, authoritative, and useful books on screenwriting. A standard by which other screenwriting books are measured, it has sold over 350,000 copies in its twenty-five-year life. Always up-to-date and reliable, it contains everything that both the budding and working screenwriter need under one cover-five books in one! A Screenwriting Primer-that provides a concise course in screenwriting basics; A Screenwriting Workbook-that walks you through the complete writing process, from nascent ideas through final revisions; A Formatting Guide-that thoroughly covers today's correct formats for screenplays and TV scripts; A Screenwriting Workbook-that walks the reader through the process of writing a screenplay; A Sales and Marketing Guide-that presents proven strategies to help you create a laser-sharp marketing plan. Among this book's wealth of practical information are sample query letters, useful worksheets and checklists, hundreds of examples, sample scenes, and straightforward explanations of screenwriting fundamentals. The seventh edition is chock-full of new examples, the latest practices, and new material on non-traditional screenplay outlets"--
How to write a screenplay, a primer -- Writing & revising scenes, a script consultant's view -- Seven steps to a stunning script, a workbook -- Proper formatting technique, a style guide -- How to sell your script, a marketing plan.
Includes bibliographical references and index.
Keywords: Motion picture authorship; Television authorship